Neuro-innate immune interactions in gut mucosal immunity. (February 2021) - Kulkarni, Subhash; Kurapati, Sravya; Bogunovic, Milena
Abstract : The gastrointestinal (GI) tract performs a set of vital physiological functions related to food and water consumption. To help regulate these complex physiological processes, the GI tract is innervated by extensive neural networks. The GI tract also serves as the largest immune organ aimed to protect hosts from harmful microbes and toxins ingested with food. It emerges that the enteric nervous and immune systems are highly integrated to optimize digestion while reinforcing immune protection. In this review, we will discuss key cellular players involved in the neuro-immune interactions within the GI mucosa with the focus on the recently uncovered neural pathways that regulate mucosal immunity in a context relevant to GI health and disease.